Untargeted Global Metabolomic Analysis Reveals the Mechanism of Tripropylamine-Enhanced Lycopene Accumulation in Blakeslea trispora - Wang, Yanlong; Wang, Yulong; Wang, Yicun; Chen, Xin; Liu, Cunping; Zhang, Meng; Liu, Keying; Zhao, Yuechao; Li, Zexu (Frontiers in Bioengineering and Biotechnology, 2021)
We previously determined that the cyclase inhibitor tripropylamine (TPA) significantly enhances lycopene accumulation in Blakeslea trispora. To elucidate the mechanism of TPA-enhanced lycopene accumulation, the untargeted metabolome of B. trispora treated with TPA was analyzed by UHPLC-Q-TOF/MS. Forty-two differential metabolites were identified, of which 15 significantly differential metabolites meeting the following parameters were screened: variable importance for the projection > 1, P < 0.05, and fold change > 1.5. The down-regulated metabolites were mainly cyclic dipeptides, bacteriostatic compounds, and lipids, while the up-regulated metabolites were mainly unsaturated fatty acid. Furthermore, the bacteriostatic ability was poor, the extracellular and intracellular pH levels were high, and hyphae with vesicles were swollen locally in B. trispora after treated with TPA. Our data suggest that the TPA enhances lycopene accumulation not only by inhibiting the cyclization of β-carotene but also by down-regulating cyclic dipeptides for quorum sensing; up-regulating unsaturated fatty acids, 1-palmitoyl-2-hydroxy-sn- glycero-3-phosphoethanolamine, and 4-hydroxybenzoate and down-regulating choline, resulting in locally swelling mycelium with vacuoles; and down-regulating bacteriostatic metabolites for metabolic flux redistribution